2016
DOI: 10.1111/cea.12776
|View full text |Cite
|
Sign up to set email alerts
|

IgE‐associated food allergy alters the presentation of paediatric eosinophilic esophagitis

Abstract: Background Links between food allergens and eosinophilic esophagitis have been established, but the interplay between EoE and IgE-associated immediate hypersensitivity to foods remains unclear. Objective We sought to determine the prevalence of IgE-associated food allergy at time of diagnosis of EoE in children and to determine if differences existed in presentation and disease compared to subjects with EoE alone. Methods EoE patients were stratified based on diagnosis of IgE-associated immediate hypersens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 31 publications
(40 reference statements)
0
30
0
1
Order By: Relevance
“…(27) We measured a rate of IgE-mediated food allergy in patients with EoE of 68%, a prevalence that is higher than previously reported. (27, 28) To ensure accurate measurement of IgE-mediated food allergy in patients with EoE, we performed a manual chart review of 100 patients. In this review, 94% of patients with both an IgE-mediated food allergy and EoE diagnosis were found to have evidence of IgE-mediated allergy to at least one food.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(27) We measured a rate of IgE-mediated food allergy in patients with EoE of 68%, a prevalence that is higher than previously reported. (27, 28) To ensure accurate measurement of IgE-mediated food allergy in patients with EoE, we performed a manual chart review of 100 patients. In this review, 94% of patients with both an IgE-mediated food allergy and EoE diagnosis were found to have evidence of IgE-mediated allergy to at least one food.…”
Section: Resultsmentioning
confidence: 99%
“…While IgE-mediated and EoE food allergy have been reported to occur together, (14, 15, 23, 28) it is difficult to estimate simultaneous occurrence of these conditions to the same food as avoidance of the causal food in IgE-mediated food allergy ameliorates EoE symptoms. Additionally, patients with EoE and IgE-mediated food allergy may display distinct clinical symptoms as compared to those without IgE-mediated food allergy, making EoE diagnosis difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This last finding has also been previously reported by Erwin et al, 17 and supports the concept that EoE patients with IgE-mediated food allergy represent a unique EoE phenotype, as we have previously reported. 18 Food sensitization seems to be a marker for a more broadly food-allergic phenotype that does not respond to FFED.…”
Section: Discussionmentioning
confidence: 99%